The application of sustainable development principles to the theory and practice of property valuation - Lorenz, David Philipp (Karlsruher Schriften zur Bau-, Wohnungs- und Immobilienwirtschaft, 2006)
This dissertation is an exploration into the fields of sustainable development, property investment and valuation. It investigates the rationale for immediately and rigorously integrating sustainability issues into property valuation theory and practice and proposes theoretical and practical options for valuers on how to address sustainability issues within valuation reports. It is argued that the perception of property as a commodity is changing to emphasize sustainable design features and performance characteristics as important determinants of a propertys worth and market value.